PERFOMA BIOCONC DALAM PENINGKATAN KUALITAS BETON - Maknoe Basoeki (AGREGAT, 2016)
ABSTRACTHigh strengh concrete is a concrete that has high compression strengh that used cement replacement materials to increased compression strengh. Cement replacement materials that usually used is silica fume and fly ash. In this paper, we observed the perfomance of high strengh concrete with OPC cement based material and silica fume as cement replacement (insertion), compared with Bioconc as micro-filler insertion, and also compared with paralel perfomance of both silica fume and Bioconc together in a concrete mix.  The variation of silica fume that used is 0%, 5%, 7,5% and 10%. Beside that, the variation of silica fume will be make as two variation, such as concrete with Bioconc and concrete without Bioconc to find out the influence of Bioconc. The w/c used is 0,25% from weight of binder, whereas to make a good workability then used superplasticizer. The variation of superplasticizer is find out by trial in the laboratory. The testing conducted at the age 1, 3, 7, 14, 21, 28 is compression strengh of paste, compression strengh of mortar, and compression strengh of concrete beside that at concrete specimen will be split and porosity test. From the result of research, the highest compression strengh at 28 days (B7,5M) is 69,71 Mpa, whereas the silica fume optimum is at 7,5%. Addition of Bioconc has no effect at concrete density but has an effect at compressive strengh. With Bioconc addition the compressive strengh increased ± 30%. Bioconc more effective in stand alone micro filler use. Mix use between Bicoconc-another filler may reduce its perfomance.Keywords : High Strengh Concrete, Compressive strengh, Bioconc, Silica fume ABSTRAKSIDalam penelitian ini akan dibuat beton mutu tinggi dengan menggunakan material dasar semen OPC dan silica fume sebagai pengganti semen. Kadar silica fume yang digunakan adalah 0%, 5%, 7,5% dan 10%. Selain itu dari kadar silica fume tersebut akan dibuat dua variasi yaitu beton dengan Bioconc dan beton tanpa Bioconc untuk mencari tahu pengaruh dari Bioconc tersebut. Faktor air semen yang dipakai adalah 0,25% dari berat binder, sedangkan untuk membuat workabilitynya bagus maka digunakan superplasticizer. Kadar superplasticizer yang digunakan dicari lewat trial pengujian di laboratorium. Pengujian yang dilakukan pada umur 1, 3, 7, 14, 21, 28 adalah uji tekan pasta, uji tekan mortar dan uji tekan beton, selain itu pada benda uji beton umur 28 hari akan dilakukan uji split beton dan uji porositas.           Dari hasil penelitian didapatkan kuat tekan beton tertinggi pada umur 28 hari (B7,5M) adalah 69,71 MPa, sedangkan variasi silica fume yang paling optimum ada pada kadar 7,5%. Penambahan Bioconc tidak berpengaruh pada berat volume beton tetapi berpengaruh pada kuat tekan beton tersebut. Dengan penambahan Bioconc maka kuat tekan beton meningkat sebesar ± 30%Kata Kunci :  Beton Mutu Tinggi, Kuat Tekan, Bioconc,  Silica fume